On-Demand Dopamine Receptor Activation via Photoresponsive Nanoparticle-Dopamine Conjugates with an Emphasis on Parkinson’s Disease - Alghamdi, Hajar (2024)
INTRODUCTION Parkinsons’ Disease is a complex neurodegenerative disease with unknown pathological mechanism associated with the reduction of dopamine content in the brain. Dopamine, in the form of L-DOPA, is used as a replacement therapy which provides temporary symptomatic relief. Long-term treatment with L-DOPA induces side effects such as involuntary movements (e.g., dyskinesia) due to the continuous and un-discriminatory exposure to dopamine. Here, we aim to address this by developing an on-demand dopamine receptor stimulation system that reduces dopamine over-exposure. To achieve that we designed a nanoparticle system displaying a photoresponsive spiropyran molecule conjugated to dopamine to stimulate activation of the D1R receptor as needed, we are able to non-invasively control dopamine receptor activation on-demand in two different cell model.